Improving teacher education for applied learning in the field of VET - Thomas Deißinger (Waxmann Verlag, 2018)
This anthology deals with vocational teacher education in Ukraine, which is a country facing many social and economic challenges. It is a result of the Erasmus+ project "Improving teacher education for applied learning in the field of VET (ITE-VET)", a capacity building project focussing on Ukraine, which lasted from October 2016 until October 2018. The project came up with the following issues which were defined as "working packages" in the context of the EU project guidelines. These issues also represent the major contents and arguments in the chapters of this book: • Ukrainian VET teacher education and VET system and analysis of their needs • Didactical input from EU countries on modern teaching • Revision of course programmes and curricula • Implementation of new forms of practice-orientation. The book compiles contributions from the Ukrainian ITE-VET project partners as well as the ITE-VET partners from the EU and from Switzerland.